2011
DOI: 10.1111/j.1540-6237.2011.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Ethical Attitudes of Business and Criminal Justice Students

Abstract: Objectives. To compare and explain differences in the ethical attitudes of criminal justice (CJ) and business students, and explore their ethical malleability. Methods. Students rated the ethical acceptability of 25 scenarios using a self-administered survey. A cross-sectional comparison of the ethical responses of sophomores and seniors measured their ethical malleability. Results. Business students were less willing to condemn unethical conduct than were criminal justice students, but were more receptive to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 56 publications
(86 reference statements)
3
19
0
Order By: Relevance
“…For example, Neubaum, Pagell, Drexler, Mckee-Ryan, and Larson (2009) found no differences in personal moral philosophy between business and non-business students. However, these findings are consistent with Segal, Gideon, and Haberfield (2011) who found that business students were more willing to accept unethical conduct than criminal justice majors and Cory and Hernandez (2014) who found that business students demonstrated higher levels of moral disengagement than humanities majors.…”
supporting
confidence: 89%
“…For example, Neubaum, Pagell, Drexler, Mckee-Ryan, and Larson (2009) found no differences in personal moral philosophy between business and non-business students. However, these findings are consistent with Segal, Gideon, and Haberfield (2011) who found that business students were more willing to accept unethical conduct than criminal justice majors and Cory and Hernandez (2014) who found that business students demonstrated higher levels of moral disengagement than humanities majors.…”
supporting
confidence: 89%
“…The greatest gains may, however, appear after the age of 24 (Segal et al 2011). More mature students may rely more on their own moral code than do younger students, who may be more vulnerable to peer pressure and other external factors (Kidwell and Kent 2008).…”
Section: Early Exposure To Ethics and Integrity Contentmentioning
confidence: 90%
“…Students with a greater tolerance for cheating and dishonesty have been shown to be more likely to behave in a dishonest manner in their subsequent work (Nonis and Swift 2001). Business students' comparatively greater tolerance for unethical behavior has been associated with self-selection and students' understanding of business as amoral (Segal et al 2011). The relationships between the evolution of values, features of the learning environment, and disciplinary norms and cultures deserve more attention in future studies.…”
Section: Economics and Business Studiesmentioning
confidence: 96%
See 2 more Smart Citations